(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Purulent inflammatory processes on the face side can lead to severe consequences if not treated in a timely and effective manner. Opening deep floors in such cases is a decisive step towards successful management. This article aims to explore the importance of this procedure to present a comprehensive and informative discussion.